Defined Criteria of Performance in Organizational Control - Baumler, John V. (Administrative Science Quarterly, 1971)
This paper reports a laboratory experiment in which a business game was played by groups of volunteer participants. The game was subject to two treatments, one altering the degree of interdependence between game participants, the other altering how it was played. The game was designed to simulate a decision-making organization, consisting of subunits with minimal or extensive interdependence, with or without defined criteria to achieve organizational control. The hypothesis that the approach to organizational control was dependent upon the degree of subunit interdependence was supported. More specifically, defined criteria were found to be appropriate only when there was minimal interdependence but inappropriate when there was extensive interdependence. Further, the evidence suggested that the viewpoints and orientations of the participants were consistent with those required by the state of organizational interdependence.